MRI Cervical Image Analysis with Fat Suppression Techniques Between Sequent Turbo Invers Recovery Magnitude (TIRM) and Fat Saturations (Fat Sat) on Degenerative Disc Disease at Haji Hospital Surabaya - Nata, Vita Arinda Ayu Putri; Astuti, Suryani Dyah; Wibowo, R. Arif (Universitas Airlangga, 2021)
This study aimed to analyze the difference of image information and determine the better image quality between the Turbo Invers Recovery Magnitude (TIRM) and Fat Saturation (Fat Sat) techniques on cervical MRI examination at Haji Hospital Surabaya. The samples of this study were one female and three male patients. The obtained data were ROI of the vertebral body tissue, intervertebral discs, spinal cord, and then calculated as SNR and CNR values. SNR and CNR values were statistically tested using Paired T-Test on SPSS 2.5. The Paired T-Test results showed a significant difference between the TIRM and Fat Sat techniques, p>0.05. SNR and CNR average values also proved that the Fat Sat technique had more optimal image quality than the TIRM technique.